A taste of Broadway : food in musical theater - Packard, Jennifer, 1970- (Studies in food and gastronomy., 2018)
Food carries symbolic importance used to define individuals, situations, and places, making it an ideal communication tool. In musical theater, food can be used as a shortcut to reveal more about a setting, character, or situation. This book looks at the role of food in popular theater musicals illustrating how food relates to the broader world.